Estimation of aloin concentration in Aloe vera L. (Aloe barbadensis Mill.) by mathematical modeling - Molero Paredes, Tamara; Kas-Danouche, Said (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Aloin is one of the secondary metabolites that gives plants of the genus Aloe spp. their healing properties. The concentration of aloin is related to the fresh mass and, its industrial purification involves laboratory processes that add extra costs to its commercialization. The objective of this research was to mathematically modelize the estimation of the aloin concentration in A. vera L. from the fresh mass. The theory of discrete perfect least squares approximations was used, considering linear and exponential approximation functions. For the tabulation of the data, the option of class mark and the average of the values ​​were used. The analyses of the approximations indicate that the exponential curves approximate the data better (with R2 = 75% and 82% for the two options, respectively) than the straight lines (with R2 = 65% and 70% for the two options, respectively). The use of these approximations is recommended to estimate the concentration of aloin in A. vera plants based on their fresh mass, facilitating the measurement of this secondary metabolite, and minimizing costs in the industrialization process.